Tenebrio molitor Larvae Feeding Strategy to Degrade Polypropylene Components from Disposable Masks - Khadijah Sayyidatun Nisa; Reynaldi Ivan Prasetya; Ibnu Maulana Hidayatullah; Abdussalam Topandi; Fatimah Azizah Riyadi; Firah Gustianda Ayu; Frederick Soetandar; Dimas Rafi Narawangsa (Equilibrium Journal of Chemical Engineering, 2024)
The surge in mask consumption during the COVID-19 pandemic led to the widespread use of disposable polypropylene masks for protection. However, the accumulation of used masks poses environmental challenges due to the slow degradation of polypropylene. Here, we investigate the potential of Tenebrio molitor larvae in degrading polypropylene masks, exploiting their synthetic polymer-breaking enzymes and associated microflora. In this study, we implemented various feeding strategies and established specific feed compositions to assess T. molitor larvae's consumption behavior towards polypropylene masks. Over a 21-day observation period, we noted a consumption rate of 0.4% of masks, with a 7.5% mortality rate among the larvae. The average daily consumption rate was 0.201 grams, resulting in a 2.3% increase in larval weight and the production of 0.4635 grams of feces. Our findings highlight the potential of T. molitor larvae as effective mask degraders. Optimizing cultivation conditions and feeding strategies may further enhance microbial diversity, potentially introducing more polypropylene degraders within T. molitor, thereby expediting mask degradation. This study emphasizes the promising role of T. molitor larvae in addressing the environmental challenges posed by the accumulation of polypropylene masks.Keywords: Mask, Degrade, Tenebrio molitor, Microflora, Polypropylene